THE INFLUENCE OF WORK CLIMATE AND FATIGUE ON THE PERFORMANCE OF SAMSAT MEDAN EMPLOYEES WITH JOB SATISFACTION AS A MEDIATION VARIABLE AT SAMSAT MEDAN UTARA - Amelia Risa, Tri; Robain, Wilchan; Rizky, M. Chaerul (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The focus of this study is to analyze job satisfaction in mediating work climate and fatigue on employee performance. A quantitative approach was chosen in this research, then the data source was obtained through distributing questionnaires to 74 employees at the North Medan Samsat. Data analysis using Sstructural equestion model (PLS SEM). The Northesearch results show that at North Medan Samsat, the work environment has a direct impact on job satisfaction. At North Medan Samsat, the work environment has a direct influence on employee performance. Directly, fatigue has no effect on employee job satisfaction at North Medan Samsat. Job satisfaction has a direct effect on employee performance at North Medan Samsat. Job satisfaction has a direct effect on employee performance at North Medan Samsat. At North Medan Samsat, job satisfaction indirectly moderates the influence of work climate on employee performance. At North Medan Samsat, job satisfaction did not significantly moderate the effect of fatigue on employee performance.